Staphylococcal slime layers and biofilm from different origins - Rodrigo Casquero Cunha; Michelle Dias Hornes da Rosa; Cleomar da Silva; Francisco Denis Souza Santos; Fábio Pereira Leivas Leite (Ciência Rural, 2019)
ABSTRACT: The genus Staphylococcus comprises some of the most important pathogenic bacteria for both humans and animals. It is responsible for bovine mastitis and canine otitis, besides being present in the microbiota of animals and as a contaminant in food. Its pathogenesis is related to the formation of capsule and biofilm, which contribute to its infectivity. The objective of this study was to observe the production of slime layer and formation of biofilm, which are related to the resistance to antimicrobial agents and presence of icaA and icaD genes, in 41 isolates of Staphylococcus spp. from different origins, provided by the Universidade Federal de Pelotas (UFPEL), Laboratório Regional de Diagnóstico (LRD). Strains of Staphylococcus spp. were cultivated in Congo red agar for capsule detection. Biofilm formation was detected using the 96-well microplate testing. Antimicrobial susceptibility testing was performed using the plate diffusion method. Part of the analyzed samples produced slime layer (36.6%) and formed biofilm (17.1%). However, six of those that formed biofilms were susceptible to the eight antibiotics tested in the antibiogram. In tests to determine the minimum bactericidal and inhibitory concentrations, gentamicin resistance of biofilm-forming strains was greater than that of non-forming strains. Ampicillin was the least effective antimicrobial drug (51%), followed by tetracycline (71%), neomycin (73%), and erythromycin (73%). Some isolates presented the icaA (6) and icaD (11) genes. Therefore, we suggested that the origin of an isolate can determine its expression of virulence factor and resistance to certain antibiotics.